2022
DOI: 10.5223/pghn.2022.25.2.138
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Factors Affecting Bone Mineral Density in Children with Celiac Disease

Abstract: Purpose Children with celiac disease (CD) are at an increased risk of low bone mineral density (BMD) owing to malabsorption of fat-soluble vitamins, inflammation, and malnutrition. This study aimed to determine the prevalence and risk factors for low BMD in Iranian children with CD. Methods This prospective cohort study examined 149 Iranian children with CD between 2011 and 2018 at Zabol University of Medical Sciences. BMD was measured using dual-energy X-ray absorptiom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Furthermore, they observed that lean mass is independently associated with BMD in these patients, explaining 11% of its variability [ 75 ]. Studies suggest that BMI can be considered as a predictor of bone density in children with CD since lower BMI is associated with lower BMD [ 76 , 77 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they observed that lean mass is independently associated with BMD in these patients, explaining 11% of its variability [ 75 ]. Studies suggest that BMI can be considered as a predictor of bone density in children with CD since lower BMI is associated with lower BMD [ 76 , 77 ].…”
Section: Introductionmentioning
confidence: 99%